Skin Wound Healing Potential and Mechanisms of the Hydroalcoholic Extract of Leaves and Oleoresin of Copaifera langsdorffii Desf. Kuntze in Rats - Gushiken, Lucas Fernando Sérgio [UNESP]; Hussni, Carlos Alberto [UNESP]; Bastos, Jairo Kenupp; Rozza, Ariane Leite [UNESP]; Beserra, Fernando Pereira [UNESP]; Vieira, Ana Júlia [UNESP]; Padovani, Carlos Roberto [UNESP]; Lemos, Marivane; Polizello Junior, Maurilio; Silva, Jonas Joaquim Mangabeira Da; Nóbrega, Rafael Henrique [UNESP]; Martinez, Emanuel Ricardo Monteiro [UNESP]; et al. (Wiley, 2017)
The wound healing is a complex process which, sometimes, can be a problem in public health because of the possibility of physical disability or even death. Due to the lack of a gold standard drug in skin wound treatment and aiming at the discovery of new treatments in skin repair and the mechanisms involved in the process, we used oleoresin (OR) from Copaifera langsdorffii and hydroalcoholic extract of the leaves (EH) to treat rat skin wounds. For that, male Wistar rats were divided into groups (n=8): Lanette, Collagenase, 10% EH, or 10% OR and, after anesthesia, one wound of 2 cm was made in the back of animals. The wounds were treated once a day for 3, 7, or 14 days and the wound areas were measured. The rats were euthanized and skin samples destined to biochemical, molecular, and immunohistochemical analysis. The results showed a macroscopic retraction of the wounds of 10% EH and 10% OR creams and both treatments showed anti-inflammatory activity. Molecular and immunohistochemical results demonstrated the activity of Copaifera langsdorffii creams in angiogenesis, reepithelialization, wound retraction, and remodeling mechanisms.